Circadian activity rhythms in relation to season, sex and interspeciﬁc interactions in two Mediterranean voles - Pita, Ricardo (2012)
Although environmental conditions and biotic interactions are widely recognized as key sources of variation in circadian activity rhythms of a broad array of vertebrates, information on their actual signi ﬁ cance outside experimental settings remains scarce. We investigated changes in circadian activity rhythms of free-ranging Cabrera voles, Microtus cabrerae, and water voles, Arvicola sapidus, in highly seasonal Mediterranean environments, and analysed how such changes were further affected by inter-sexual and interspeciﬁc interactions. Cabrera voles were largely diurnal, with a unimodal peak around midday during the wet season, whereas during the dry season activity was reduced during the hot midday period and increased strongly at dawn and dusk. Water voles also had a marked bimodal crepuscular pattern during the dry season, but this was much attenuated during the wet season, when they were comparatively more diurnal. Activity patterns varied little between the sexes, although with a tendency for higher overall activity by male Cabrera voles (dry season only) and water voles, possibly because of intersexual interactions involving seasonal shifts from monogamy to facultative polygyny in Cabrera voles, and year-round polygyny in water vole. Within each season, Cabrera voles appeared to change their activity patterns in the presence of water voles, reducing overall activity and shifting activity peaks towards diurnal (dry season) or crepuscular (wet season) time periods less used by water voles. Overall, this study provides evidence for the strong role of seasonal changes in environmental conditions and interspeciﬁc interactions in driving variation in the activity patterns of Mediterranean voles under natural conditions.